Determinan Keuangan Keperilakuan Heuristic dan Herding Analysis terhadap Keputusan Investasi Berbasis Syariah - Rozak, Abdul; Nugraha, Nugraha; Sari, Maya (Jurnal Manajemen dan Keuangan, 2023)
Increasing investor interest in investing will certainly increase transaction activity in capital market, so that it will have an impact on the smooth running of company's operations. Business activities that run well and safely will increase the rate of economic growth. Relatively affordable investment capital as launched by Indonesia Stock Exchange since 2015 by holding the "Yuk Nabung Saham" campaign aimed at inviting investors to invest by buying stocks or other instruments on a regular basis at Capital Market. Throughout 2021, the growth in the number of investors has increased very significantly, especially for novice investors from millennial generation to invest in several sharia instruments. This study aims to examine heuristic bias (representativeness, overconvidence) and herding financial behavior models of sharia-based investment decisions for millennials in the West Java region. Quantitative research with a causal design was applied using a purposive sampling technique by collecting a questionnaire of 180 respondents. Meanwhile, the data analysis method uses the PLS software application. The results showed that financial variable representativeness behavior had a significant negative effect on investment decisions of millennial generation in West Java, while financial variables of overconfidence and herding behavior had a significant positive effect on investment decisions of millennial generation in the West Java region.